Immunogenicity and safety of Gardasil among mid-adult aged men (27–45 years)—The MAM Study. Issue 42 (13th October 2015) - Giuliano, Anna R.; Isaacs-Soriano, Kimberly; Torres, B. Nelson; Abrahamsen, Martha; Ingles, Donna J.; Sirak, Bradley A.; Quiterio, Manuel; Lazcano-Ponce, Eduardo
Highlights The quadrivalent HPV vaccine was administered to mid-adult men ages 27–45 years. 100% of men seroconverted to each of the four HPV vaccine components. Immune response to vaccine in men ages 27–45 was comparable to that in younger men. Antibody response did not differ by age group or sexual orientation. No serious adverse events attributable to vaccination were observed.